Analyzing the keys to the design of a mobile application for physical activity for school and out-of-school use from the perspective of adolescents, teachers, coaches, managers, and experts - Adrián Mateo-Orcajada; Lucía Abenza-Cano; Pedro Ángel López-Miñarro; Lourdes Meroño; Ana María Gallardo-Guerrero; María de la Trinidad Morales-Belando; Noelia González-Gálvez; Alejandro Espeso-García; Tomás Abelleira-Lamela; Nerea Gómez-Cuesta; Antonio Joaquín García-Velez; Mario Albaladejo-Saura; et al. (PLoS ONE, 2025)
No previous research has analyzed the opinion of adolescents, teachers, coaches, managers, and mobile app experts, on the usefulness and functionality of mobile apps for use by adolescents. For this reason, the objectives of this research were: to discover their opinion about the physical activity apps currently available; and to determine the elements and characteristics that they consider most relevant to find in a physical activity app that can be used for a longer period of time. Eight focus groups were carried out in which a total of 38 adolescents (mean age: 13.74 ± 1.24 years old), 29 teachers, coaches, and managers (mean age: 35.27 ± 2.81 years old), and 10 experts (mean age: 43.18 ± 4.22 years old) participated. The most relevant results regarding the apps available include limitations in their functionality and design, as well as in the information provided and the requirements, which means that they are not designed exclusively for adolescents. Regarding the demands for a specific app for adolescents, the participants highlighted gamification as the main element, as it is key to user engagement, as well as the possibility of recording physical activity along with other healthy habits. Challenges, competitions or the possibility of observing progress should also be present in the application as they also influence user engagement and motivation. Adolescents also highlighted a multimedia section, privacy and rewards, while for professionals the inclusion of feedback, the facilitation of work and a fast interface for use in the school environment were key.